An agent-based modeling tool supporting bioenergy and bio-product community communication regarding cellulosic bioeconomy development. (October 2022) - Yang, Pan; Cai, Ximing; Hu, Xinchen; Zhao, Qiankun; Lee, Yuanyao; Khanna, Madhu; Cortés-Peña, Yoel R.; Guest, Jeremy S.; Kent, Jeffrey; Hudiburg, Tara W.; Du, Erhu; John, Steve; et al.
Abstract: The emergence of the cellulosic bioeconomy requires not only adequate technological, economic, and policy advances, but also effective communication and coordination among the multiple stakeholders in the bioeconomy community. Aiming to facilitate stakeholder communication and collaboration for cellulosic bioeconomy growth, an agent-based model is developed as a community communication tool in this study. The tool simulates the behaviors and interactions of key stakeholders, as well as the responses and interactions between the stakeholders and biophysical, socioeconomic, and environmental conditions. The agent behavior rules are developed and validated based on behavior and economic theories and information attained from a stakeholder focus group study and a land use survey. A pilot study in a Central Illinois watershed shows stakeholder synergies, i.e., positive feedback loops across multiple stakeholders. The modeling tool's role in facilitating community communication is demonstrated via the focus group study. A comparison of policy scenarios suggests that the cellulosic bioeconomy development is fastest under a portfolio of policies combining the views of the multiple stakeholders. Critically, subsidy for small-scale bio-facilities is essential as it rapidly initializes an early market for cellulosic feedstocks and the adoption of Miscanthus. The communication tool is applied to bringing stakeholders and researchers together to develop shared visions, assess barriers, and explore solution portfolios to initialize and speed up the regional cellulosic bioeconomy. Highlights: Agent-based model presents a communication tool for cellulosic bioeconomy community. The model is validated with mixed theoretical knowledge and survey data. Stakeholder synergies enabling cellulosic bioeconomy emergence are identified. A shared vision among stakeholders is illustrated via the communication tool. Subsidies for small-scale bio-facilities effectively promote cellulosic bioeconomy.